The organic stratigraphy of Ontong Java Plateau Tuff correlated with the depth‐related presence and absence of putative microbial alteration structures. Issue 3 (7th December 2018) - Purvis, Graham; van der Land, Cees; Sano, Naoko; Cockell, Charles; Barlow, Anders; Cumpson, Peter; Lopez‐Capel, Elisa; Gray, Neil
Abstract: Structures in geological samples are often interpreted as fossilised life; however, such interpretations are equivocal, as abiotic processes can be invoked to explain their presence. Thus, additional lines of chemical evidence are invaluable in confirming or refuting such morphological evidence. Glass shards in tuff from the Ontong Java Plateau (OJP) contain microtubular structures that are in close proximity to functionalised nitrogen substituted aromatic compounds that may be indicative of the chemical remnants of biological activity. The organic composition of the OJP tuff containing microtubular alteration structures was compared with tuff without such features. In addition, organic matter associated with horizons with compacted remnants of woody material buried in the OJP tuff and overlying pelagic calcareous foraminifer sediment were also characterised, to ascertain the provenance of the organic matter found in the OJP tuff. As a further control, the organic material in submarine and terrestrial basalts from other locations were also characterised providing further evidence to support the view that the organic matter in the OJP tuff is authigenic. Carbon–nitrogen chemistry was detected across all OJP tuff samples irrespective of the presence or absence of microtubular features, but was not detected in either the wood material, the overlying pelagic sediments or in the basalts from other locations. The results indicate no direct link between the OJP nitrogenous organic compounds and the presence or absence of microtubular features.